Pemanfaatan Game Edukasi Berbasis Speech Recognition untuk Mengurangi Language Anxiety pada Mata Pelajaran Bahasa Inggris - Rickman Roedavan; Bambang Pudjoatmodjo; Agus Pratondo (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
SMK ICB (Yayasan Insan Cinta Bakti), located at Jl. Pahlawan No.19B, Cihaur Geulis, Kec. Cibeunying Kaler, Kota Bandung, Jawa Barat 40122, faces significant challenges related to English language anxiety among students. An initial survey revealed that 85% of the total 180 students experience difficulties in English subjects. To address this issue, a prototype educational game based on Speech Recognition, developed by a team of lecturers and students from Telkom University, will be tested to help reduce language anxiety among students. This game integrates with the microphone on a laptop/computer, detecting and recording accurate sentences spoken by the students as scores. The utilization of this prototype educational game is expected to serve as an additional supplement for English learning and help reduce language anxiety for SMK ICB students.